Erosão da Camada Limite Planetária em Região Tropical (Rondônia) - Rble3, 1994 - Lyra, Roberto F. F.; Junior, Rosiberto S. S.; Ramos, Diogo N. S.; Rabelo, Flávia D.; Amorim, Marney C. A. L. (Ciência e Natura, 2011)
.